Nutritional Characteristics and Quality of Eggs from Laying Hens Fed on a Dried Papaya Peel Meal Diet - Leke, Jein Rinny; Sompie, Florencia Nery; Wantasen, Erwin; Tallei, Trina Ekawati (ANIMAL PRODUCTION, 2018)
The objectives of this study were to analyze the eggs nutritional characterics and quality from laying hens fed with diried papaya (Carica papaya L) peel meal diets. A total 200 brown laying hens strain MB 402 (42 week-old). The design used in this study was  a The objectives of this study were to analyze the eggs’ nutritional characteristics and quality from laying hens fed with dried papaya (Carica papaya L) peel meal diets. A total of 200 brown laying hens strain MB 402 (42 week-old) were used in this experiment. The design used in this study was a completely randomized design (CRD) consisting of 5 treatments and 4 replications (10 hens each). The treatments consisted of dried papaya peel meal (DPPM) 0%, 3%, 6%, 9% and 12%. Total feeding trial was 8 weeks. The parameters recorded included egg weight (g/bird)), egg yolk weight (g/bird), yolk index (%), albumen index (%), egg yolk color, egg cholesterol (mg/100g), egg crude protein (%), egg crude fat (%), egg white crude protein (%), egg yellow fat (%),  eggshell calcium (%), eggshell phosphorus (%), blood cholesterol (mg/dl), blood LDL cholesterol (mg/dl), and blood HDL cholesterol (mg/dl) of the laying hens. The results showed that feeding birds with 12 %   increased egg yolk weight, egg yolk color, egg crude fat, egg yellow fat, egg cholesterol, egg shell calcium, egg shell phosphor, blood cholesterol, blood HDL. Moreover there were no significant differences in egg weight, yolk index , albumen index, egg crude protein, egg white crude protein and blood LDL. In Conclusion, DPPM diets can be fed to the laying hens up to 12 % to produce eggs without negative effects on the egg quality.ransomized design (CRD) consisting of 5 treatments and 4 replications (10 hens each). The treatments made use of dried papaya peel meal (DPPM) 0%, 3%, 6 %, 9 % and 12 %. Total feeding trial was 8 weeks . The parameters recorded included egg weight (g/bird), egg yolk weight (g/bird), yolk index (%), albumen index(%), egg yolk calor, egg cholesterol (mg/100g), egg crude protein (%), egg crude fat (%), egg white crude protein (%), egg yellow fat (%), eggshell calsium (%), eggshell phosphorus (%), blood cholesterol (mg/dl), blood LDL Cholesterol  (mg/dl), and blood HDL cholesterol (mg/dl) of the laying hens, The results showed that feeding dried papaya peal meal in cinclusion 12 % increased egg yolk weight, egg yolk color, egg crude fat, egg yellow fat, egg cholesterol,  egg shell calsium, egg shell prosphor, blood cholesterol, blood HDL. Moreover there were no significant diffirence in egg weight, yolk index, albumen index, egg crude protein, egg white crude protein and blood LDL. In conclusion DPPM diets can be fed to the laying hens up to 12 % to produce eggs without negative effects on the egg quality.